Hot electron transport in wurtzite-GaN: effects of temperature and doping concentration. (July 2018) - Acharyya, Aritra
Abstract: The hot electron transport in wurtzite phase gallium nitride (Wz-GaN) has been studied in this paper. An analytical expression of electron drift velocity under the condition of impact ionization has been developed by considering all major scattering mechanisms such as deformation potential acoustic phonon scattering, piezoelectric acoustic phonon scattering, optical phonon scattering, electron-electron scattering and ionizing scattering. Numerical calculations show that electron drift velocity in Wz-GaN saturates at 1.44 × 10 5 m/s at room temperature for the electron concentration of 10 22 m −3 . The effects of temperature and doping concentration on the hot electron drift velocity in Wz-GaN have also been studied. Results show that the saturation electron drift velocity varies from 1.91 × 10 5 –0.77 × 10 5 m/s for the change in temperature within the range of 10–1000 K, for the electron concentration of 10 22 m −3 ; whereas the same varies from 1.44 × 10 5 –0.91 × 10 5 m/s at 300 K for the variation in the electron concentration within the range of 10 22 –10 25 m −3 . The numerically calculated results have been compared with the Monte Carlo simulated results and experimental data reported earlier, and those are found to be in good agreement.